Kinetics of surfactant desorption at an air-solution interface - Morgan, C E (Langmuir : the ACS journal of surfaces and colloids, 2012)
The kinetics of re-equilibration of the anionic surfactant sodium dodecylbenzene sulfonate at the air-solution interface have been studied using neutron reflectivity. The experimental arrangement incorporates a novel flow cell in which the subphase can be exchanged (diluted) using a laminar flow while the surface region remains unaltered. The rate of the re-equilibration is relatively slow and occurs over many tens of minutes, which is comparable with the dilution time scale of approximately 10-30 min. A detailed mathematical model, in which the rate of the desorption is determined by transport through a near-surface diffusion layer into a diluted bulk solution below, is developed and provides a good description of the time-dependent adsorption data. A key parameter of the model is the ratio of the depth of the diffusion layer, H(c), to the depth of the fluid, H(f), and we find that this is related to the reduced Péclet number, Pe*, for the system, via H(c)/H(f) = C/Pe*(1/2). Although from a highly idealized experimental arrangement, the results provide an important insight into the "rinse mechanism", which is applicable to a wide variety of domestic and industrial circumstances